TANGGUNG GUGAT INVESTOR REKSADANA TERHADAP INFORMASI SUSPENSI PT. BIBIT ATAS PRODUK REKSADANA PT. SINARMAS ASSET MANAGEMENT - Ruroh, Siti Mas (Journal of Private and Economic Law, 2023)
Law No. 8 of 1995 on Capital Market regulates the obligation of public company issuers and other parties to apply the principle of openness. Article 1 number 25 of Law No. 8 of 1995 on Capital Market explains that "The Principle of Openness is a general guideline that requires Issuers, Public Companies, and other parties subject to this law to inform the public promptly all material information about its business or its effects that may affect the decision of investors on the intended effect and or the price of such securities." Based on the background, the problem formulation is what the basis of Sinarmas Asset Management Inch. liability for claiming the suspension information conducted by BIBIT.Inch . The purpose of Sinarmas Asset Management Inch. liability is to seek compensation for the suspension information conducted by BIBIT.Inch The research method used in this study is the normative juridical research method using a statutory approach, and conceptual approach, and deductive analysis method. The conclusion is a violation of the principle openness conducted by BIBIT.Inch is a mutual fund selling agent that has a cooperation contract with the Investment Manager of Sinarmas Asset Management.Inch as the manager of the securities portfolio by conveying incorrect suspension information and improper advice to investors when purchasing mutual fund securities in fintech applications sent by email has violated Article 79 paragraph (1) of the Capital Market Law and fulfilled the elements of unlawful acts in Article 1365 of the Civil Code. So based on Article 81 paragraph (1) BIBIT.Inch is responsible for the non-implementation of the principle of openness that harms mutual fund investors and Sinarmas Asset Management.Inch. Sinarmas Asset Management.Inch may sue for damages to BIBIT.Inch with the obligation to prove the consequences of BIBIT.Inch based on Article 1365 of the Civil Code jo Article 111 of the Capital Market Law by fulfilling the evidence contained in Article 1866 of the Civil Code. Keywords: Liability, Disclosure Principles, PT Sinarmas Asset Management and PT. BIBIT